2020
DOI: 10.1002/jia2.25631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonsuppressed viral load and associated factors among HIV‐positive adults receiving antiretroviral therapy in Eswatini, Lesotho, Malawi, Zambia and Zimbabwe (2015 to 2017): results from population‐based nationally representative surveys

Abstract: Introduction: The global target for 2020 is that ≥90% of people living with HIV (PLHIV) receiving antiretroviral therapy (ART) will achieve viral load suppression (VLS). We examined VLS and its determinants among adults receiving ART for at least four months. Methods: We analysed data from the population-based HIV impact assessment (PHIA) surveys in Eswatini, Lesotho, Malawi, Zambia and Zimbabwe (2015 to 2017). PHIA surveys are nationally representative, cross-sectional household surveys. Data collection inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…All participants were on antiretroviral therapy, with a mean CD4 count of 448.6 cells/mL (SD, 280.8) and 97.5% were virally suppressed (< 1,000 copies/mL). 33 On average, between five and seven images were needed to be taken to obtain three images of satisfactory quality. Images from the first 94 participants were evaluated by three off-site colposcopists.…”
Section: Resultsmentioning
confidence: 99%
“…All participants were on antiretroviral therapy, with a mean CD4 count of 448.6 cells/mL (SD, 280.8) and 97.5% were virally suppressed (< 1,000 copies/mL). 33 On average, between five and seven images were needed to be taken to obtain three images of satisfactory quality. Images from the first 94 participants were evaluated by three off-site colposcopists.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying which PLHIV are at greatest risk of disengagement from within subpopulations is a high priority. Population HIV impact assessments (PHIAs) in five southern African countries have reported that among people with nonsuppressed viral load, marriage, female sex, shorter ART duration, higher CD4 count and alcohol use were associated with higher odds for interrupted ART [ 31 ]. Many may have been women who were offered rapid ART initiation during an antenatal program following Option B+ guidelines.…”
Section: The Cyclical Cascade Can Help Target Interventionsmentioning
confidence: 99%
“…7 Considering that people living with HIV infection (PLWHIV) who are not on ART generally develop profound immunodeficiency over 7 years for adults and 5 years for children and that the rate failure of ART is 11%, we estimated the population of PLWHIV at risk. 8 TB rates were taken from the WHO Global report 2019, and we derived the pulmonary TB survivors. Asthma prevalence in adults living in Kinshasa was assumed to apply to the whole country.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%